July 1931 [Fred Louis's family and friends] - Fred Louis:::::: (1931)
Page of Fred Louis's scrapbook containing photographs of Ett, Elsie, HL, G. S., M, Wing, Beulah, Mary Quong, M. E. M., Mary E. M., Fred, Perozz, Margaret R., Merce. D., Toby, Stel, Young, Fay, Helen R., Toby, Ed, Billy, Jay, and pet dogs Tootsie and Tiay.